Zum Verbraucherverständnis von Alpen- und Weidemilch; Consumer Understanding of the Terms Alpine Milk and Pasture-raised Milk - Ramona Weinrich; Sarah Kuḧl; Anke Zuḧlsdorf; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2016)
– In recent years in the course of product differentiation more and more dairy products have been introduced promising additional benefits for consumers. The present article analyses the consumers' understanding of the products alpine milk and pasture-raised milk by means of two empirical studies. Currently, both product designations are legally unprotected terms. Therefore, producers and marketers implement the labelling with very different product concepts. Against this background it is empirically analysed how consumers understand alpine milk and pasture-raised milk. Do consumers think that cows giving the milk for alpine milk are kept in a certain geographical region? And does pasture-raised milk mean to them that dairy cattle have access to pasture and if yes during which period? The results of the case studies show that consumer expectations with respect to products which are advertised with unobservable process characteristics are very high which could lead to consumer disappointment.
Keywords: 330